2011
DOI: 10.2176/nmc.51.673
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Unilateral Open-Door Laminoplasty With Titanium Miniplates Through Newly Designed Hydroxyapatite Spacers -Technical Note-

Abstract: A newly designed hydroxyapatite (HA) spacer for cervical laminoplasty is provided with a hole through which the titanium miniplate is passed. A new method of unilateral open-door laminoplasty with titanium miniscrew and miniplate through this HA spacer is described. Twenty-two patients with cervical stenotic disorders were treated by this procedure. Only the predominantly affected side of the laminae is exposed. The supraspinous and interspinous ligaments and the deep muscle layer in the contralateral side are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The ratio of JOA score improvement rates was 47.8% in the plate group and 42.4% in the suture group, which is similar to others reported in the literature. 14,15 The JOA score increase was higher in the plate group, but it was not statistically signifi cant between the 2 groups. Using a plate in open-door laminoplasty may not contribute to neurological improvement more than using sutures would.…”
Section: A 6b 6c 6dmentioning
confidence: 86%
“…The ratio of JOA score improvement rates was 47.8% in the plate group and 42.4% in the suture group, which is similar to others reported in the literature. 14,15 The JOA score increase was higher in the plate group, but it was not statistically signifi cant between the 2 groups. Using a plate in open-door laminoplasty may not contribute to neurological improvement more than using sutures would.…”
Section: A 6b 6c 6dmentioning
confidence: 86%
“…Recently, several authors have presented new technique of cervical laminoplasty using hydroxyapatite laminar spacers and titanium miniplates. Tanaka et al reported that hardware failure or screw loosening did not occur during 36.3 months mean follow-up period after a single open door laminoplasty using hydroxyapatite laminar spacers and titanium miniplates in 22 patients 31) . Goto et al reported that hardware failure or screw loosening did not occur during 24.3 months mean follow-up period after a single open door laminoplasty using hydroxyapatite laminar spacers and titanium miniplates in 25 patients 5) .…”
Section: Discussionmentioning
confidence: 99%
“…The modification of cervical laminoplasty and halfcut spinous process at the proximal and distal of the opening is still not widely used. [3][4][5][6] Nevertheless, the outcome of this modified technique is preferable in maintaining the anteroposterior diameter of spinal canal as well as reducing the displacement of guttered laminae. 7 Furthermore, the neck motion, especially in the younger age, will also be maintained.…”
Section: Resultsmentioning
confidence: 99%